Descriptive and spatial analysis of bycatch in tuna purse-seine fishery in the colombian Pacific Ocean, with an elasmobranch approach - Vladimir Puentes; Dalia C. Barragán-Barrera; Karina Bohrer Do Amaral; Fabian D. Escobar; Luis A. Zapata; Emiliano Zambrano; Carlos G. Barreto; José Tavera; Carlos J. Polo; Jairo Altama; Angelica S. Moreno; Iván F. Benavides (Ocean and Coastal Research)
Bycatch species are as important as target species in the challenge of comprehensive fishery management. This is especially the case for vulnerable species such as elasmobranchs in offshore areas of the Colombian Pacific Ocean (CPO), for which information is scarce and long-term databases are used. Therefore, this study aimed to characterize the bycatch in tuna purse-seine fishery with an elasmobranch species approach using fishery data from 2000 to 2019. A total of 59 bycatch species were identified, including 27 bony fishes, 22 elasmobranchs, two mollusks, four sea turtles, and four dolphins. The total bycatch percentage was 20.8%, with elasmobranchs accounting for less than 5%. Fish aggregating devices (FADs) and class 6 vessels recorded the highest percentage of bycatch. Bony fish bycatch was mainly obtained from the border of Ecuador until 4° N across the CPO. Elasmobranchs were captured throughout the CPO, showing differences by vessel class and fishing method. The silky shark Carcharhinus falciformis was the most caught species. Elasmobranch spatial abundance and capture hotspots showed the highest values towards the northern coast, in offshore areas of Gorgona Island, southwards in offshore areas, and around Malpelo Island. FADs captured the highest number of bycatch species compared with other fishing methods, such as Tuna Associated with Dolphins (DEL), Natural Floating Objects (NAT), and Tuna not Associated (NoAs). Management recommendations for bycatch species in this fishery are provided in the CPO.